Fluorescence Imaging of Peripheral Nerves by a Nav1.7-Targeted Inhibitor Cystine Knot Peptide - Gonzales, Junior; Demetrio de Souza Franca, Paula; Jiang, Yan; Pirovano, Giacomo; Kossatz, Susanne; Guru, Navjot; Yarilin, Dimitry; Agwa, Akello J; Schroeder, Christina I; Patel, Snehal G; Ganly, Ian; King, Glenn F; et al. (Bioconjugate chemistry, 2019)
Twenty million Americans suffer from peripheral nerve injury caused by trauma and medical disorders, resulting in a broad spectrum of potentially debilitating side effects. In one out of four cases, patients identify surgery as the root cause of their nerve injury. Particularly during tumor resections or after traumatic injuries, tissue distortion and poor visibility can challenge a surgeon's ability to precisely locate and preserve peripheral nerves. Intuitively, surgical outcomes would improve tremendously if nerves could be highlighted using an exogeneous contrast agent. In clinical practice, however, the current standard of care-visual examination and palpation-remains unchanged. To address this unmet clinical need, we explored the expression of voltage-gated sodium channel Nav1.7 as an intraoperative marker for the peripheral nervous system. We show that expression of Nav1.7 is high in peripheral nerves harvested from both human and mouse tissue. We further show that modification of a Nav1.7-selective peptide, Hsp1a, can serve as a targeted vector for delivering a fluorescent sensor to the peripheral nervous system. Ex vivo, we observe a high signal-to-noise ratio for fluorescently labeled Hsp1a in both histologically prepared and fresh tissue. Using a surgical fluorescent microscope, we show in a simulated clinical scenario that the identification of mouse sciatic nerves is possible, suggesting that fluorescently labeled Hsp1a tracers could be used to discriminate nerves from their surrounding tissues in a routine clinical setting.Twenty million Americans suffer from peripheral nerve injury caused by trauma and medical disorders, resulting in a broad spectrum of potentially debilitating side effects. In one out of four cases, patients identify surgery as the root cause of their nerve injury. Particularly during tumor resections or after traumatic injuries, tissue distortion and poor visibility can challenge a surgeon's ability to precisely locate and preserve peripheral nerves. Intuitively, surgical outcomes would improve tremendously if nerves could be highlighted using an exogeneous contrast agent. In clinical practice, however, the current standard of care-visual examination and palpation-remains unchanged. To address this unmet clinical need, we explored the expression of voltage-gated sodium channel Nav1.7 as an intraoperative marker for the peripheral nervous system. We show that expression of Nav1.7 is high in peripheral nerves harvested from both human and mouse tissue. We further show that modification of a Nav1.7-selective peptide, Hsp1a, can serve as a targeted vector for delivering a fluorescent sensor to the peripheral nervous system. Ex vivo, we observe a high signal-to-noise ratio for fluorescently labeled Hsp1a in both histologically prepared and fresh tissue. Using a surgical fluorescent microscope, we show in a simulated clinical scenario that the identification of mouse sciatic nerves is possible, suggesting that fluorescently labeled Hsp1a tracers could be used to discriminate nerves from their surrounding tissues in a routine clinical setting.